Strategic cassava R and D planning activities to maximize future impact - Henry, Guy; Best, R. (International Center for Tropical Agriculture, 1993)
Financial and human resources for national and international cassava R and D have traditionally been a scarce good. In order to optimize the return on research investment, cassava R and D needs to be well focused, generating appropriate technology components to maximize adoption and subsequent impact. Both international and national research institutions have been aware of this and have emphasized the development of methodologies and strategies to accomplish this. ISNAR has developed a Strategic Research Planning exercise that can be applied to refocus and reorganize cassava R and D activities and/or programs. In the paper an example is given of such a planning excercise and the case of cassava research in Vietnam. While the latter exercise can generate recommendations for the more general structural and organization issues, another case is presented of a strategy followed by CIAT in collaboration with Latin American national cassava program, in which cassava production, utilization and market research activitites, are integrated, which has been both efficient and effective in maximizing impact at the producer, processor and consumer level.